DIAGNOSIS OF TOLERANCE IN HIGH SCHOOL STUDENTS AS A BASIC CRITERION OF RESPECTFUL ATTITUDE TOWARDS REPRESENTATIVES OF DIFFERENT ETHNICITY (ON THE MATERIALS OF THE CRIMEA REGION) (Pedagogy of Higher and Secondary Education, 2011)
The article summarizes data of the research about the generated level of tolerance of the Crimean students as a basic criterion of the respectful treatment of representatives of different ethnic groups.
Keywords: tolerance; students; respectful treatment; ethnos